Socioeconomic status is associated with process times in the emergency department for patients with chest pain - Sebastian Herlitz; Joel Ohm; Henrike Häbel; Ulf Ekelund; Robin Hofmann; Per Svensson (Journal of the American College of Emergency Physicians Open)
Abstract Objective Emergency department length of stay (EDLOS) is linked to crowding and patient outcomes whereas worse prognosis in low socioeconomic status remains poorly understood. We studied whether income was associated with ED process times among patients with chest pain. Methods This was a registry‐based cohort study on 124,980 patients arriving at 14 Swedish EDs between 2015 and 2019 with chest pain as their chief complaint. Individual‐level sociodemographic and clinical data were linked from multiple national registries. The associations between disposable income quintiles, whether the time to physician assessment exceeded triage priority recommendations as well as EDLOS were evaluated using crude and multivariable regression models adjusted for age, gender, sociodemographic variables, and ED‐management circumstances. Results Patients with the lowest income were more likely to be assessed by physician later than triage recommendations (crude odds ratio [OR] 1.25 (95% confidence interval [CI] 1.20–1.29) and have an EDLOS exceeding 6 h (crude OR 1.22 (95% CI 1.17–1.27). Among patients subsequently diagnosed with major adverse cardiac events, patients with the lowest income were more likely to be assessed by a physician later than triage recommendations, crude OR 1.19 (95% CI 1.02–1.40). In the fully adjusted model, the average EDLOS was 13 min (5.6%) longer among patients in the lowest income quintile, 4:11 [h:min], (95% CI 4:08–4:13), compared to patients in the highest income quintile, 3:58 (95% CI 3:56–4:00). Conclusions Among ED chest pain patients, low income was associated with longer time to physician than recommended by triage and longer EDLOS. Longer process times may have a negative impact due to crowding in the ED and delay diagnosis and timely treatment of the individual patient.